The Influence of “Artificial Intelligence + Human–Computer Interaction” on Teachers’ Psychological Changes in Academic Management in Colleges - Guan, Honghai; Chen, Qingli; Han, Song; Zhang, Baoge (Frontiers in Psychology, 2021)
The purpose was to analyze the psychological changes of teaching staff in the academic management of local colleges, and briefly explore the role of teaching staff in the development of the social economy and colleges. In the environment of artificial intelligence and human-computer interaction, first, the relevant theories of teaching staffs’ psychological status and the characteristics of teaching staff in college academic management were analyzed and expounded. Next, the way of the questionnaire was selected to analyze the psychology of teaching staff in college academic management at different ages, professional titles, academic qualifications, disciplines and teaching years. The results showed that the mental health level of college teachers was lower than the current national adult standard; the mental health level of female teachers in colleges was higher than that of male teachers; the p value of mental health of college teachers with different ages, professional titles, education, disciplines and teaching years was greater than 0.05, indicating that there was no significant difference; the p value of professional academic and mental health was less than 0.01, indicating that there was a significant correlation, that was, teachers' professional academic exerted a significant impact on teachers' mental health. In short, under the background of artificial intelligence and human-computer interaction’s rapid development, higher education was moving forward with high quality, and more attention should be paid to the psychological changes of college teaching staff.